Constraints on the major sources of dissolved organic carbon in Alpine ice cores from radiocarbon analysis over the bomb-peak period - May, Barbara Luise; Wagenbach, Dietmar; Hoffmann, Helene; Legrand, M.; Preunkert, S.; Steier, P. (Journal of geophysical research. Atmospheres, 2013)
Radiocarbon (14C) has proven to be a powerful tool in distinguishing modern and fossil fuel sources contributing to organic aerosols. By applying this concept to ice core records of the dissolved organic carbon (DOC) fraction, we developed a setup dedicated to the extraction of DOC from Alpine ice core samples for 14C microanalysis. With respect to the difficulties and limitations of this analytical method, it is shown that a total process blank mass of (6 ± 3) μgC with a 14C signature of (0.71 ± 0.17) can be obtained, corresponding to a minimum sample size between 200 g for industrial and 800 g for pre-industrial ice. Radiocarbon analyses of eight DOC ice core samples from the high accumulation glacier Col du Dôme (European Alps) were mainly performed over the bomb-peak period. These data, being associated with snow deposition over the summer half-years, show an overall mean fossil contribution of (25 ± 9) %. Adaptation of the DO14C values to the atmospheric 14CO2 record revealed that the biogenic input to ice core DOC is associated with a fast recycling biospheric component, likely linked to a turnover time of less than 3 years.